The impetus in the reconstruction of the symbol (2015)
The Lógos is the originating identity from which the structure of any entity, whether by emanation, scission and / or foundation; while reason is the manifest expression of the creative intelligence of the Demiurge, the nous of the cosmos. Lógos is both the inspiration as reveals the object of revelation.